A mixed method study of tuberculosis case management in hospitals of West and Central Java, Indonesia - Prihartono, Nurhayati; Hadi, Ella N.; Wuryaningsih, Caroline E.; Saraswati, Lintang D.; ., Yovsyah (International Journal Of Community Medicine And Public Health, 2017)
Background: Indonesia as the secondlargest contributor of tuberculosis (TB)has adopted the WHOrecommendation through DOTS strategy to reducedisease burden in both government and private hospitals. Effectiveness of DOTS implementation in healthcare centers has been reported. However,few studies found that the TB treatment success rate in hospitals was still low.The objectives of the study were to assess case detection and the implementation of DOTS strategy in hospital. Methods: Study was conducted in 8 hospitalsin West Java and Central Java that had implemented DOTS strategy during a two-year period (2007-2008). Mixed methods were used to obtain data on treatment strategy quantitatively and its exploration qualitatively, particularly the practice performed by hospital staff and the patient’s experience. Results: Hospitals didnot refer many new TB cases to healthcare centers. All patients, treatment observers and the heads of DOTS team of the private hospitals stated that medication was always available at the hospital. Some public hospitals reported lack of stock of OAT due to large patient numbers.Seven out of the 8 hospitals had allocated treatment observers.Public and private hospitals had achieved treatment success rate of 61 to 74% for smear-positive and negative cases. However, there was a high proportion of cases that defaulted from treatment, the majority of which was among smear-negative cases in public hospital (29%). Conclusions: Overall success rate of TB treatment in hospital was low. Strengthening of TB case management in hospital through improved training of health-care personnel is needed to reduce the burden of TB in Indonesia.